Overview of the economic and social importance of the livestock sector in Cyprus with particular reference to sheep and goats - Markou, M.; Papachristoforou, Christakis (My University, 2006)
The value, in current prices, of livestock production in Cyprus exceeds the amount of CY£ 160 million and accounts for about 42% of the value of total agricultural production. The country is self-sufficient in milk and milk products, eggs, pig and poultry meat, while production covers the demand for beef by 70–75% and for sheep and goat meat by 90%. Over the last 40 years, the production of meat increased more than 10-fold, of milk 6-fold and of eggs doubled. These achievements were the result of the gradual transformation from low to high input production systems in an effort to improve productivity to satisfy the increasing demand, to reduce production risks associated with frequent droughts, to decrease pressure on the environment from overgrazing, and to lower production costs. Today, in dairy cattle, pigs and poultry, the production is based on a small number of high input and medium to large size commercial farms using employed labour force, while in sheep and goats, farms are smaller and rely on family labour. In cattle and sheep, one predominant breed in each species is utilized for production, while in goats, two breeds and their crosses are used. Pig and poultry farms rely on imported breeds and hybrids. The per capita consumption of livestock products is among the highest in Europe leaving little room for further increases. The present trends relate to quality aspects of livestock products, introduction of new technology, improved production management, reduced costs and production methods friendly to the environment.
Keywords: Cyprus livestock production; Present situation; Future prospects